ANALISIS KEWENANGAN KANTOR IMIGRASI JAKARTA BARAT TERHADAP ORANG ASING PELAKU PROSTITUSI ONLINE: Analysis Of The Authority Of The West Jakarta Immigration Office Towards Foreigners Involved In Online Prostitution - Andrian Syah; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2026)
Globalization and advances in information technology have increased the mobility of foreign nationals (FNs) to Indonesia, while simultaneously facilitating online prostitution practices involving the misuse of residence permits. The research problem in this study is how the authority of the West Jakarta Immigration Office is implemented in handling foreign nationals involved in online prostitution. The research employs a normative legal method with statutory and conceptual approaches and adopts a descriptive-analytical design, combining literature studies of primary, secondary, and tertiary legal materials with empirical data derived from official reports and media coverage of relevant cases. The findings reveal that the West Jakarta Immigration Office predominantly applies administrative immigration measures, such as deportation and entry bans, rather than criminal sanctions. Although this approach is considered efficient in enforcing immigration law, it faces limitations in anticipating offenders’ evolving modus operandi that exploit digital platforms. The effectiveness of enforcement is strongly influenced by inter-agency coordination, the capacity to identify foreign nationals, and adherence to human rights principles. In conclusion, the exercise of immigration authority in West Jakarta emphasizes preventive and administrative measures but requires strengthened oversight mechanisms, cross-agency integration, and enhanced utilization of technology to more effectively curb online prostitution practices.